Predictors of in-hospital mortality and poor functional outcomes in patients who underwent surgical evacuation of intracerebral hemorrhage - Saal-Zapata, Giancarlo (2022)
Objective: To determine predictors of in-hospital mortality and poor functional prognosis in patients undergoing surgery for intracerebral hemorrhage. Materials and Methods: Clinical records, operative reports, and cerebral CT scans of patients with intracerebral hemorrhage from March 2018 to March 2020 were analyzed. Univariate and multivariate logistic regression analyses were performed for determining independent predictors of in-hospital mortality and poor functional prognosis at discharge. Results: In-hospital mortality was 33.7% (n= 31 patients). Independent predictors for mortality were female sex (OR= 3.01, p= 0.031) and Glasgow score <8 on admission (OR= 3.19, p= 0.031). A poor functional prognosis after the intervention was found in 77 patients (83.7%). Independent risk factors for a poor functional prognosis were score >3 in the modified Rankin scale (OR= 15.5; p= 0.01), and preoperative motor deficit (OR= 8.95; p= 0.042). Conclusions: In patients with intracerebral hemorrhage who were surgically treated, high morbidity and mortality rates were found. Female sex and clinical factors, such as consciousness condition and functional status on admission were independent predictors for in-hospital mortality and poor functional prognosis.